Are Vaginal Suppositories of Quercus infectoria fruit hulls Effective on the Signs and Symptoms of Vulvovaginal Candidiasis? A Triple-Blind Controlled Clinical Trial - Simbar, Masoumeh; Mahboubi, Mohaddese; Motlagh, Asieh Azadpour; Kiani, Zahra; Rashidi, Farzaneh; Nazarpour, Soheila; Majd, Hamid Alavi- (Current Traditional Medicine, 2026)
AimsThis study aims to compare the effects of Quercus Infectoria Fruit Hulls (QIFH) with Clotrimazole vaginal suppositories on the signs and symptoms of vulvovaginal candidiasis.Background/IntroductionVulvovaginal Candidiasis (VVC) is an infection caused by Candida species. Although the antimicrobial effects of QIFH have been confirmed, there is no clinical study on its effects on VVC.MethodsOne hundred married women (aged 18-45 years) with complaints of vulvar pruritus or burning were recruited for a triple-blind clinical trial at a health center affiliated with Khorramabad University of Medical Sciences. After a definitive diagnosis of vulvovaginal candidiasis, the eligible women were randomly divided into two groups: one receiving QIFH vaginal suppositories (n=45) and the other receiving Clotrimazole vaginal suppositories (n=45). The patients were instructed to use the medications for 7-10 nights. The symptoms and signs of VVC were compared before and after treatment within each group and between the two groups. The data were analyzed using SPSS 24, employing both parametric and non-parametric tests with a 95 percent confidence interval.ResultsThe symptoms and signs of VVC, including pruritus, burning and irritation, vaginal discharge, vaginal redness, and swelling with white, thick discharge, significantly improved in both groups after treatment (p<0.001). There were no significant differences between the two groups of QIFH vaginal suppository users and Clotrimazole users regarding the relief of signs and symptoms after treatment (p>0.05).DiscussionA study comparing Clotrimazole and QIFH vaginal suppositories found that Quercus infectoria extract effectively treated candida and reduced its growth. Treatment with QIFH significantly improved pruritus symptoms. The tannin ingredient in QIFH's tannins acted through various mechanisms, providing therapeutic and antioxidant effects. QIFH could be an alternative for VVC treatment for women.ConclusionThe QIFH vaginal suppository was as effective as Clotrimazole in treating the symptoms and signs of VVC without any adverse effects. Given the prevalence of VVC and the similarities in the treatment processes with QIFH and Clotrimazole, it can be concluded that QIFH may be an appropriate alternative for VVC treatment for women who prefer to use herbal medicine.Clinical Trial Registration No. IRCT20190306042943N2.
Keywords: Quercus infectoria